Mother knowledge and health-seeking behavior towards childhood TB - Islam, Qazi Shafayetul; Ahmed, Syed Masud; Islam, Md. Akramul; Shatil, Tanvir; Siddique, Zakia Sultana (BRAC Research and Evaluation Division (RED), 2019)
Introduction: BRAC in association with NTP recently started the community-based child TB programme. So far, no independent study has been conducted to explore the extent to which the objectives of the programme have been achieved in terms of raising knowledge about child TB, and changing health-seeking behavior. This study uses quantitative method to evaluate the knowledge, attitude and practices of mothers towards childhood TB. Methods: The study was a cross-sectional in nature and it included mothers (257 in numbers) as respondents on behalf of child TB patients. Structured and semi-structured questionnaires were applied to elicit information. The study involved interviewing 157 BRAG health workers (Shasthya Sebika. SS) to explore their knowledge regarding childhood TB. Results: Both BRAG health workers (47%) and mothers (35%) did not have adequate knowledge about the primary risk source for child TB (closeness of contact). The knowledge of SSs (13-38%) and mothers (7-40%) regarding BCG and isoniazid therapy as a preventive strategy of TB was inadequate and similar. Both the health workers and the mothers had comprehensive knowledge about sputum test (67-78%) and X-ray (63-77%) for detecting TB in children except about tuberculin test (27-28%). Clinical symptoms like low grade fever (80-88%) and chronic cough (73-83%) were well known to them, but weight loss was not noted profusely (20-54%). Majority of SSs (61 %) and the mothers (47%) perceived that TB in children was dangerous. About half of SSs (50%) had high stigma. One-fourth of mothers (27%) did not want to disclose their child's TB due to fear and 35% of them became frustrated due to it. The time between the onset of symptoms and diagnosis of TB among children was 60 days (mean). The majority of child TB patients were aged between 11-14 years (46-65%) followed by 6-10 years (23-28%). More than one-third of the children (38%) had exposure to TB patients at home, and 16% to neighborhood TB patients. About 4 7% of mothers' children received treatment from informal providers at first time. The providers commonly prescribed cough syrup (41%), tablet for fever (40%) and antibiotics (37%). About 55% of mothers went to providers more than four times before diagnosis of her child's TB. The majority of detected cases were diagnosed at district (23%) and private hospitals (30%). A significant majority of children (85%) referred to BRAG for treatment. Conclusion: Programme should organize special training on child TB for awareness of health workers. Strong collaboration between NTP and local communities are required to develop social mobilization, and sensitization in disseminating childhood TB information. Healthcare providers need to set schedule to provide education, increase awareness of contact case screening, early identifying and treating TB infection and disease in children.